Adherence and discontinuation of optimal heart failure therapies according to age. (3rd October 2022) - Garred, C H; Zahir, D; Butt, J H; Ravn, P B; Bruhn, J; Gislason, G; Fosboel, E L; Torp-Pedersen, C; Petrie, M C; McMurray, J J V; Koeber, L; Schou, M
Abstract: Background: Guideline-recommended disease-modifying pharmacological therapies for heart failure (HF) with reduced ejection fraction are underutilized, particularly among elderly patients. Purpose: We examined adherence with and discontinuation of evidence-based HF pharmacotherapy, comprising of angiotensin-converting enzyme inhibitors (ACEi)/angiotensin-II receptor blockers (ARB), beta-blockers (BB) and mineralocorticoid receptor antagonists (MRA), according to age. Methods: Using Danish nationwide registries, we included patients with a first HF diagnosis between 2011 and 2018. Patients were stratified into three age groups, <65 years (reference group), 65–79 years, and ≥80 years. The average daily drug dose was calculated as median proportions of target doses one year after inclusion. Adherence was estimated by the proportion of days covered (PDC), i.e., the total number of days with the drug available for a patient alive for the whole first year of the follow-up period. Discontinuation was defined as a break of >90 days, and the 5-year risk of discontinuation according to age groups was estimated with the Aalen-Johansen estimator. Multivariable Cox regression models were used to evaluate the treatment discontinuation rate according to age groups. Results: We included a total of 29, 482 patients (<65 9, 449 (25.4% female), 65–79 13, 746 (33.1%), ≥80 6, 287 (46.3%)). Advancing age was associated with lower median proportions of daily target doses (ACEi 100%, 88%, 63%; ARB 75%, 67%, 50%; BB 75%, 56%, 44%), and lower adherence (ACEi/ARB 79.1%, 77.5%, 69.4%; BB 79.1%, 78.6%, 73.8%), in the <65, 65–79 and ≥80 age groups respectively, one year after inclusion. Age ≥80 was associated with a higher 5-year risk of discontinuation; cumulative incidence, ACEi/ARB 41%, 44%, 51%; BB 38%, 35%, 39%, in the same age group order as above (adjusted hazard ratio: ACEi/ARB 1.60 [95% CI, 1.51–1.69]; BB 1.33 [95% CI, 1.25–1.41]). Conversely, the risk of discontinuation of MRAs differed little with age (<65 50%, 65–79 54%, ≥80 56%), although MRA initiation in the most elderly was less frequent (<65 33%, 65–79 33%, ≥80 22%). Conclusion: Among a nationwide cohort of HF patients, advanced age was associated with lower proportions of daily target doses, lower adherence, and a higher rate of discontinuation of ACEi/ARB and BBs. Focus on treatment adherence and optimal dosages among elderly HF patients could improve outcomes. Funding Acknowledgement: Type of funding sources: None.